The Multi-Agency Response Approach To The Management Of Oil Spill Incidents: Legal Framework For Effective Implementation In Nigeria - Olaniyan, Ayobami (Journal of Sustainable Development Law and Policy, 2025)
The devastating effects of oil spill incidents on humans and the environment can be overwhelming. Effects such as loss of life, forced displacements, loss of property and serious health risks cannot be overlooked. Also, the long-term damage to the ecosystem, sea life and biodiversity are some of the long-term consequences of an oil spill incident. Thus, a swift response to oil spill incidents is always necessary in order to minimize these effects. The multi-agency response approach emphasizes a holistic and coordinated involvement of several related institutions and entities in order to ensure adequate response to any category of oil spill incident. Even though the multi-agency approach seems to be already embedded in relevant legislation on oil spill control and containment in Nigeria, its operationalization has been less impressive. This article discusses the practical relevance and implementation of multiagency response to oil spills in Nigeria. It appraises the efficacy of relevant Nigerian legislation providing for multi-agency response to oil spill control and containment in Nigeria, highlights the weaknesses of the current regulatory arrangement, and suggests legal reforms to make the multi-agency response approach more efficient and effective in Nigeria. This includes the need to harmonize several overlapping legislations and governance institutions on oil spill response and management to ensure coherence and systemic integration.